A simple method for enrichment of β-lactoglobulin from bovine milk whey involving selective hydrolysis by two fungal protease preparations. (30th January 2022) - Ha, Minh; El-Din Bekhit, Alaa; McConnell, Michelle; Carne, Alan
Highlights: Fungal protease preparations were used to hydrolyse bovine acid whey fraction. The proteases left the beta-lactoglobulin (β-Lg) intact. The intactness of β-Lg was confirmed using several analyses. Resulted hydrolysate of other whey proteins exhibited enhanced bioactivity. Abstract: Two commercially available food grade fungal protease preparations (Fungal Protease 31, 000 and Fungal Protease 60000) were found to hydrolyse bovine acid whey proteins but left the beta-lactoglobulin (β-Lg) intact under the processing conditions used. Comparative analysis before and after hydrolysis of bovine acid whey, by 1D- and 2D-PAGE, RP-HPLC and intact-mass mass spectrometry showed that the β-Lg remains intact and in high yield after hydrolysis by the fungal proteases. The β-Lg could be separated from the whey protein peptide hydrolysate by ultrafiltration. Subjecting whey fraction to hydrolysis with the fungal protease preparations provides a procedure, under relatively mild conditions, to generate a highly enriched β-Lg fraction. β-Lg is recognised as a valued material in the food, pharmaceutical and cosmetic industries due to its properties such as gelling and foaming. The enriched β-Lg preparation would also have application in areas such as nanoencapsulation.